Effects Of Lower Multılooped Arches Durıng Treatment Of Extractıon Cases Wıth Edgewıse Technıque - Hakan N. İşcan; Elçin Gür (Turkish Journal of Orthodontics, 1988)

(untitled)
In this study carried on a total of 22 lateral cephalometric films, taken prior to and after 0.014 inch lower multilooped arch, from 11 four first premolar extraction cases whose orthodontic treatments were started with 0.018 inch slot standard edgewise technique; mean increases of 1.0 mm. in Holdaway difference, 1.1 mm. in the distance of lower incisor to NB line, mean extrusion of 0.7 mm. at the lower incisors, a mean anchorage loss of 1.2 mm. and increase of 0.8 degree in the mandibular plane angle during the study period of 0.237 ± 0.08 years (2 months 29 days) were found to be statistically significant